2016
DOI: 10.1021/acs.est.6b02601
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Environmentally Persistent Free Radicals on α-Al2O3

Abstract: Metal oxides exhibit catalytic activity for the formation of environmentally persistent free radicals (EPFRs). Here, we investigate, via first-principles calculations, the activity of alumina α-AlO(0001) surface toward formation of phenolic EPFRs, under conditions relevant to cooling down zones of combustion systems. We show that, molecular adsorption of phenol on α-AlO(0001) entails binding energies in the range of -202 kJ/mol to -127 kJ/mol. The dehydroxylated alumina catalyzes the conversion of phenol into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 79 publications
1
37
0
Order By: Relevance
“…Due to the presence of heavy toxic metals such as Cr, Cd and Pb, EAFD imposes serious environmental and health concerns [2,3]. For example, various metal oxides species in EAFD promote the formation of the notorious environmental persistent free radicals such as phenoxy [4]. The main elements of EAFD are zinc and iron, which vary in the range of 2-46% and 10-45%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the presence of heavy toxic metals such as Cr, Cd and Pb, EAFD imposes serious environmental and health concerns [2,3]. For example, various metal oxides species in EAFD promote the formation of the notorious environmental persistent free radicals such as phenoxy [4]. The main elements of EAFD are zinc and iron, which vary in the range of 2-46% and 10-45%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The study provides a detailed investigation of the interaction of a phenol molecule with different hydration coverage of alumina clusters and therefore offers important insights into the role of the surface adsorbed water in the catalytic activity of alumina toward the generation of adsorbed phenoxy radicals. The present study expands on our recent investigation, 51 in which we considered a dehydrated a-Al 2 O 3 (0001) surface. Overall, this study has a three-fold aim; (i) to report modes of interaction of phenol with different hydration coverages of alumina clusters, (ii) to compare between the catalytic activity of hydrated and dehydrated alumina clusters toward the formation of the adsorbed phenolate via two distinct pathways; namely direct ssion of the phenol' O-H bond and elimination of water molecules and to (iii) to construct a simplied kinetic model for the conversion of phenol into adsorbed phenoxy radicals.…”
Section: Introductionmentioning
confidence: 77%
“…These values also agree with the results obtained in our recent study. 51 We found that, phenol molecule strongly interacts with the dehydrated a-Al 2 O 3 (0001) surface via physisorbed binding energies in the range of À127 kJ mol À1 to À202 kJ mol À1 , leading to the formation of an adsorbed phenolate with a modest activation energy of 48 kJ mol À1 . (Fig.…”
Section: Reaction Of Phenol With Dehydrated Alumina Clustermentioning
confidence: 85%
See 1 more Smart Citation
“…Additionally, phenoxy radicals that are important intermediates in the thermal degradation of biomass and biofuel may be reported in an "en-ol" resonance structure (mesomer) in which the unpaired electron is located on an ortho-carbon denoted as o − C∕ ; or para carbon denoted as p − C∕ ; or a "keto" resonance structure in which the unpaired electron is associated with the oxygen, denoted as O∕ -as detailed in literature [15,40]. Radical species formed from thermal degradation events have generally been referred to as environmentally persistent free radicals ( EPFRs ) and represent a class of reactive species that have prolonged life time even under ambient environmental conditions [41]. These radicals may be precursors for a group of environmentally persistent volatile organic pollutants such as phenols, dioxins and benzofurans which can easily be converted to the most toxic environmental pollutants ever known-polychlorinated dioxins and polychlorinated dibenzo furans ( PCDD∕Fs ) in presence of small amounts of chlorine and a transition metals such as iron or copper and/or their corresponding oxides [41,42].…”
Section: Elemental Composition Of Char and Electron Paramagnetic Spectramentioning
confidence: 99%